The Influence of Service Quality and Satisfaction on Interest in Return Visits of Inpatient Patients at Bekasi Regency Hospital - Sutra Gustianingrum; MGS Aritonang; Nurita Andayani (Jurnal Indonesia Sosial Teknologi, 2024)
This success can be achieved if it provides quality services that have an impact on patient satisfaction and will further affect the interest in re-visiting. This study aims to determine the effect of service quality on patient satisfaction and the influence of both on re-visitation interest. This research was conducted using a quantitative descriptive method. The study sample was taken using a purposive sampling technique of 100 respondents. Data were collected through questionnaires, and analysis using SEM (Structural Equation Model). The results showed that good service quality has a positive and significant effect on patient satisfaction, creating a satisfying experience and building trust. Patient satisfaction, as a result of adequate service quality, also has a positive and significant impact on repeat visit intention.